49 accommodating doctors safety; where are we at?. (31st October 2017) - Akbar, Tahir; Osanlou, Orod; Byrne, Hayleigh; Osanlou, Rostam
Abstract : Background: The media has highlighted "tired doctors make mistakes" and growing numbers accidents have been reported involving tired junior doctors. This work aims to establish the proportion of NHS trusts providing accommodation to doctors after long shifts, the ease of accessing this accommodation and any financial impact this may have and ultimately to improve safety, for both junior doctors and their patients. Method: A freedom of information (FOI) request was sent out to all NHS trusts in England, Wales and Northern Ireland, to establish if they offered accommodation and how easy it was to access including, cost, if this needed to be paid upfront, any subsidisation and how much notice was needed to obtain a room. Results: Within the time frame provided, 101* of 199 trusts responded, of which 76% provided accommodation, with 48% providing it free of charge. For those that charged, prices ranged from -£8–£65, with a median cost -£27/night. Of those that responded, only 3% subsidised rooms and 75% required the cost to be paid upfront. Using the median cost of accommodation, we calculated the proportion of a trainee's enhancement that would be spent on accommodation should a trainee require to use it for their placement based on a 1:9 rota. This was 99.8% for FY1, 72.8% for CT1% and 57.5% for ST3 and above. Conclusions: The 2016 junior doctor contract stipulates a 37% enhancement on base pay for night shifts worked. As shown, this cost of accommodation is a significant proportion of junior doctor's salary and is not sustainable. We have highlighted the difference in trust policy regarding accommodation. Our aim is to improve the working life and safety of junior doctors by highlighting this issue to trusts as well as push for an agreeable nationwide fixed tariff for accommodation. Keywords: Presenter: Dr Hayleigh Byrne.